2010
DOI: 10.1007/s11258-010-9736-7
|View full text |Cite
|
Sign up to set email alerts
|

Leaf litterfall patterns of perennial plant species in the arid Patagonian Monte, Argentina

Abstract: The objective of this study was to investigate the variation in leaf litterfall patterns of desert plant species in relation to the intra-and interannual variation of precipitation. We collected the leaf litterfall of 12 representative species of the dominant life forms in the arid Patagonian Monte (evergreen shrubs, deciduous shrubs, and perennial grasses) at monthly intervals during three consecutive years. All shrub species showed a marked seasonality in the pattern of leaf litterfall, but the date of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…In this study, litterfall production presented inter-and intra-annual variation and was correlated with precipitation and evapotranspiration rates. The average annual rainfall is responsible, at least in part, for the variability in primary net productivity between years and consequently, for the variation in litterfall production in both forests (Münster-Swendsen, 1987;Bo Pedersen and Bille-Hansen, 1999) and deserts (Strojan et al, 1979;Lauenroth and Sala, 1992;Alvarez et al, 2009;Campanella and Bertiller, 2010). In the present study, a decrease in litterfall production occurred during the dry season, approximately four months after the highest monthly precipitation rates were recorded.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…In this study, litterfall production presented inter-and intra-annual variation and was correlated with precipitation and evapotranspiration rates. The average annual rainfall is responsible, at least in part, for the variability in primary net productivity between years and consequently, for the variation in litterfall production in both forests (Münster-Swendsen, 1987;Bo Pedersen and Bille-Hansen, 1999) and deserts (Strojan et al, 1979;Lauenroth and Sala, 1992;Alvarez et al, 2009;Campanella and Bertiller, 2010). In the present study, a decrease in litterfall production occurred during the dry season, approximately four months after the highest monthly precipitation rates were recorded.…”
Section: Discussionsupporting
confidence: 43%
“…Litterfall production is considered one of the main routes of nutrient transfer from the vegetation to the soil (Vitousek, 1984;Búrquez et al, 1999;Vital et al, 2004). Therefore, quantifying litterfall pools is essential to properly understand the structure and function of tropical forests (Bray and Gorham, 1964;Vital et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to examine how felled litters vary with climate inasmuch as previous litterfall studies have indicated that climate can significantly affect the forest litterfall. Typhoons (Lin et al, 2003), floods (Haase, 1999), temperature (Kouki and Hokkanen, 1992), precipitation (Hennessey et al, 1992;Pedersen and BilleHansen, 1999;Campanella and Bertiller, 2010), and a combination of temperature and precipitation (Saarsalmi et al, 2007) were proved to be significant factors regulating forest litterfall. But despite the increasing amount of research relative to litterfall dynamics in cool-temperate forests (Tripathi et al, 2006;Xu and Shibata, 2007;Watanabe et al, 2012), the influence of changing climate on the litterfall production has been largely ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Particulate organic matter represents the youngest and most active organic material in the soil and its decomposition is heavily dependent on residue input and weather conditions (Martínez et al, 2017). Campanella and Bertiller (2010) studied leaf litterfall patterns of perennial plant species (shrubs and grasses) in arid Patagonia and demonstrated that in most shrub species, and Poa ligularis (present in the soil sampling sites) increased precipitation was related to increased litter production. Moreover, Chuquiraga erinacea , one of the shrubs species with the greatest coverage and abundance in the studied transects (19.8% and 0.6 plants m −2 ; unpublished data), has the main peak of leaf litter production in winter‐early spring (Campanella & Bertiller, 2010).…”
Section: Discussionmentioning
confidence: 99%